PENGARUH PELAYANAN KESEHATAN PASIEN RAWAT JALAN TERHADAP KEPUASAN PASIEN RSU PALANG BIRU KUTOARJO: Studi Kasus pada Pasien Poli Anak - Effa Anjula (STIE Rajawali Purworejo, 2023)
This study aims to examine the influence of service quality on the satisfaction of patients who visit RSU Palang Biru Kutoarjo. Data collection techniques in this research were obtained by means of observation, interviews, questionnaires, documentation and library studies. people. Data collection methods through observation, interviews, questionnaires, documentation and library studies. Data analysis techniques use , simple linear regression, t test and determination test research results. The simple linear regression line equation produces the equation Y= 29,271+0.601X1. The constant coefficient value results in 29,271. This means that if the value of the Health Services variable is 0 (zero), then the level or magnitude of the Patient Satisfaction variable is 29,271. The Health Services variable has a coefficient of 0.601. A value of 0.601 means that if the value of the Health Services variable increases by 1 unit and other variables are considered fixed or constant then the level of Patient Satisfaction is 0.601. Determination analysis produces an R Square of 0.326, this number is called the coefficient of determination value. The determination value is 0.326 or 32.6%. This figure means that 32.6% of patient satisfaction can be explained using the Health Service variable. Meanwhile, the remaining 67.4% (100%-32.6%) is likely influenced by other variables not studied such as comfort, facilities, etc. .Hypothesis testing (t test) shows that the Health Service variable (X1) has a positive and significant effect on Patient Satisfaction (Y). This means that the null hypothesis which states that there is no positive and significant influence between the Health Service variable on Patient Satisfaction is rejected and the working hypothesis (H1) which states that there is a positive and significant influence between Health Service and Patient Satisfaction is accepted.